2009
DOI: 10.5713/ajas.2009.80527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crude Protein Levels in Total Mixed Rations on Growth Performance and Meat Quality in Growing Korean Black Goats

Abstract: This study was carried out to investigate effects of crude protein (CP) levels in total mixed rations (TMR) on growth performance and meat quality in growing Korean black goats. Thirty-six 6-month-old growing black male goats (initial body weight = 17.95±0.13 kg) were used. The goats were randomly divided into four treatments and 9 animals were allotted to each treatment. In terms of treatments, CP levels in TMR were 14, 16, 18, and 20% of dry matter (DM) and all diets were isocaloric (2.4 Mcal ME/kg DM). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Similarly, in this study showed that there was significant difference in daily total DM intake among treatments. The result from present study was similar to those from Broderick (2003) who reported that feed intake of DM was lower on 15.1% CP than at 16.7% and 18.4% CP and earlier studies reported that daily CP intake increased as CP level in feed increased (Hwangbo et al 2009). Means in the same row with different superscripts differ (P < 0.05).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, in this study showed that there was significant difference in daily total DM intake among treatments. The result from present study was similar to those from Broderick (2003) who reported that feed intake of DM was lower on 15.1% CP than at 16.7% and 18.4% CP and earlier studies reported that daily CP intake increased as CP level in feed increased (Hwangbo et al 2009). Means in the same row with different superscripts differ (P < 0.05).…”
Section: Discussionsupporting
confidence: 82%
“…Daily total DM intake ranged from 10.2 to 14.3 kg/d and dairy CP and organic matter (OM) intake significantly increased with increasing dietary CP level (P < 0.05). In general, it is well known that feed intake increases as dietary CP level increases (Argüello et al 2003;Broderick & Reynal 2009;Hwangbo et al 2009). Similarly, in this study showed that there was significant difference in daily total DM intake among treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lammers and Heinrich (2000) fed heifers ration with LP, MP and HP and reported that ADG was improved by 9% in heifers fed a diet containing HP-to-ME ratio. The same results were observed in sheep and goats (Hwangbo et al, 2009;Sultan et al, 2010). Increasing dietary CP levels causes a change in the process of intake and digestion in the rumen and also improves absorption of by-pass proteins that contribute to metabolisable protein available for growth (Nolan and Leng, 1983).…”
Section: Omdmentioning
confidence: 61%
“…The castration at 4 mo age resulted in lower glycogen content which may be responsible for lower hue angle value (Ripoll et al, 2008). Higher value of drip loss in S2 group was due to lower water holding capacity of meat as water holding capacity was decreased due to lower growth performance of the S2 (Hwangbo et al, 2009). Other carcass attributes showed the non-significant effect of the class of animals because the sex and castration did not result in fat deposition at this age of animals and could be due to fattening period was less than 5 months (Zamiri et al, 2012).…”
Section: Discussionmentioning
confidence: 97%